Conducting Pharmaceutical Inspections in the Russian Federation to Ensure Compliance with the EAEU GCP Requirements Is an Accepted Necessity - A. A. Trapkova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2023)
Inspections of pharmaceutical market participants to verify their compliance with good practice requirements are integral to good regulatory practices of the Member States of the Eurasian Economic Union (EAEU). The framework for Good Clinical Practice (GCP) inspections is outlined in Decision No. 78 of the Council of the Eurasian Economic Commission of November 3, 2016.This interview with Alla A. TRAPKOVA, Deputy General Director of the Scientific Centre for Expert Evaluation of Medicinal Products of the Ministry of Health of the Russian Federation, provides information on the importance, objectives, and rules of conducting GCP inspections.